(untitled) (REMUNOM, 2026)
Introduction: Obesity is a chronic and multifactorial condition associated with metabolic and functional alterations. Bariatric and metabolic surgery is an effective strategy for weight control and the management of comorbidities; however, gaps remain regarding early changes in muscle strength after the procedure, an important aspect for functionality and surgical effectiveness. Objective: To evaluate factors associated with the evolution of handgrip strength and surgical effectiveness in the postoperative period following bariatric and metabolic surgery. Methods: This prospective cohort study included patients undergoing bariatric and metabolic surgery in a public hospital. Handgrip strength, body weight, body mass index (BMI), physical activity level, use of protein supplements, and engagement in resistance exercise were assessed in the preoperative period and at 1 and 3 months postoperatively. Surgical effectiveness was evaluated at 1 and 3 months after surgery. Results: A total of 52 patients were evaluated. A significant reduction in body weight and BMI was observed throughout the follow-up period. Postoperative time was associated with a lower probability of adequate handgrip strength compared with the preoperative period. In contrast, the surgical effectiveness score increased over the follow-up period. Both outcomes were not associated with age, type of surgery, use of protein supplementation, physical activity, or BMI. Conclusion: Follow-up time was significantly associated with handgrip strength, with a lower probability of adequate strength in the postoperative period following bariatric and metabolic surgery compared with the preoperative period. Surgical effectiveness increased significantly over time; however, this improvement was not reflected in handgrip strength, and the other variables analyzed showed no significant association in the multivariable models.